Image recall using a large scale generalized Brain-State-in-a-Box neural network - Oh, Cheolhwan; Żak, Stanisław H. (Zielona Góra: Uniwersytet Zielonogórski)
An image recall system using a large scale associative memory employing the generalized Brain-State-in-a-Box (gBSB) neural network model is proposed. The gBSB neural network can store binary vectors as stable equilibrium points. This property is used to store images in the gBSB memory. When a noisy image is presented as an input to the gBSB network, the gBSB net processes it to filter out the noise. The overlapping decomposition method is utilized to efficiently process images using their binary representation.
Keywords: associative memory; Brain-State-in-a-Box (BSB) neural network; overlapping decomposition; image recall